Silicon-based material for battery negative plate and preparation method of silicon-based material
By using a silicon-based material composed of a silicon-based core, an intermediate layer and a carbon cladding layer in a lithium-ion battery, and grafting specific functional groups on the carbon cladding layer, the battery capacity attenuation caused by volume expansion during the cycle is solved, and higher cycle stability and specific capacity are achieved.
Patent Information
- Application Number
- CN202411934715.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
Smart Images

Figure CN119742342A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a silicon-based material for a battery negative electrode sheet and a preparation method thereof. Background Art
[0002] With the development of society, human beings are increasingly dependent on energy, and the large-scale exploitation of traditional non-renewable energy will cause serious environmental crises, greatly affecting the earth's environment on which human beings depend for survival. In order to solve the current energy security problems and improve the current environmental situation, it is of great significance to develop environmentally friendly new energy materials and related energy storage systems that are pollution-free and sustainable. Among the many types of energy storage batteries, nickel-chromium batteries have greater environmental pollution and a short life span, which limits the application scope of 3C products. Although nickel-hydrogen batteries are relatively environmentally friendly, their high prices make it difficult to meet the needs of actual production. Lithium-ion batteries, which have outstanding advantages, are widely used in various mobile devices with their long service life, low self-discharge and environmental friendliness, and play an important role in modern energy storage technology.
[0003] Silicon, which is abundant in the earth's crust, can be used as anode material in lithium-ion batteries. Its theoretical specific capacity is more than ten times that of graphitized carbon cathode materials. However, the reaction between silicon materials and lithium ions during repeated cycles will cause a huge volume expansion (more than 300%). The huge expansion and contraction can easily lead to the peeling of electrode materials on the current collector and the collapse of the conductive network. It is also easy to expose silicon particles to the electrolyte, destroying the solid electrolyte membrane (SEI membrane) on the interface, and ultimately causing the battery capacity to decay faster. The development of high-energy and long-life lithium-ion batteries has a long way to go.
[0004] At present, there are several main ways to solve the above problems: (1) Nano-sizing, nano-sizing Si particles to reduce volume expansion and improve cycle performance; (2) Porosity, reserving volume expansion space for Si particles and alleviating volume expansion; (3) Composite with carbon materials to optimize capacity and first efficiency; (4) Introducing a medium to alleviate expansion; (5) Using Si oxide to reduce its volume expansion.
[0005] For example, Chinese Patent Application CN105118974A discloses a silicon-based anode material, which is a carbon-coated silicon / carbon nanofiber. It includes: carbon nanofibers loaded with silicon nanoparticles and a carbon coating layer that provides secondary protection for the silicon nanoparticles exposed on the surface of the carbon nanofibers. Its preparation method includes the following steps: (1) Electrospinning: Mix polyacrylonitrile and silicon nanoparticles and dissolve them in N,N-dimethylformamide solvent. After stirring and ultrasonic dispersion, a uniformly dispersed electrospinning solution is obtained. Electrospin the obtained electrospinning solution to obtain silicon / polyacrylonitrile nanofibers; (2) Carbonization: Pre-oxidize the silicon / polyacrylonitrile nanofibers obtained in step (1) in an air atmosphere, and then carbonize them in an argon atmosphere to obtain silicon / carbon nanofibers; (3) Sucrose coating by impregnation method: Immerse the silicon / carbon nanofibers obtained in step (2) into a sucrose solution, and then take them out and dry them in the air to obtain sucrose-coated silicon / carbon nanofibers; (4) Secondary carbonization: Carbonize the sucrose-coated silicon / carbon nanofibers obtained in step (3) in an argon atmosphere to obtain carbon-coated silicon / carbon nanofibers; The method described in this solution has a complex preparation process and insufficient improvement in performance. Again, Chinese Patent Application CN117438562A discloses a silicon-based material, its preparation method, a negative electrode sheet, and a battery. The silicon-based material includes a core and a coating layer. The core includes a silicon-containing material, and the coating layer is formed on at least part of the surface of the core. The coating layer includes metal fluoride and A x TiO y , where A includes one of Li, Na, K, Mg, Al, Fe, Ca, and Ba, x satisfies 0 < x ≤ 2, and y satisfies 0 < y ≤ 5. The silicon-based material provided in this application has high high-temperature resistance performance, can improve the charge and discharge efficiency and cycle stability performance of the battery at high temperatures, but in this application, the carbon coating layer and the intermediate layer are only coated by physical calcination, and may fall off during the cycling process, resulting in instability of the anode material.
[0006] Therefore, it is of great significance to develop a silicon-based material for battery negative electrode sheets with reduced swelling, good structural and cycling stability, and high capacity in the art. Summary of the Invention
[0007] Aiming at the deficiencies of the prior art, the purpose of the present invention is to provide a silicon-based material for battery negative electrode sheets and its preparation method. The silicon-based anode can significantly reduce the volume expansion of the silicon-based material, and at the same time help to form a stable and uniform SEI film during the battery cycling process, and has good ionic conductivity, specific capacity, and cycling stability.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] A silicon-based material for battery negative electrode sheets, the silicon-based material sequentially includes a silicon-based core, an intermediate layer, and a carbon coating layer from inside to outside;
[0010] The carbon coating layer is connected to the middle layer through a chemical bond, and a functional compound is grafted onto the surface of the carbon coating layer.
[0011] Preferably, the silicon-based core is silicon monoxide, and the intermediate layer is fluoride.
[0012] Preferably, the carbon source in the carbon coating layer is carboxymethyl cellulose, and the functional compound is 2-mercaptobenzothiazole and allylthiourea.
[0013] The present invention also protects a method for preparing the silicon-based material for a negative electrode sheet of a battery as described above, comprising the following steps:
[0014] S1, mixing silicon oxide and fluoride, and then calcining to obtain a silicon-based core coated with an intermediate layer;
[0015] S2, adding the silicon-based core of the coated intermediate layer obtained in step S1 to an ethanol aqueous solution, then adding γ-aminopropyltriethoxysilane, stirring to react, filtering, washing, and drying after the reaction is completed to obtain a solid product; then adding the solid product to deionized water, then adding carboxymethyl cellulose, EDC, and NHS to react at a constant temperature, filtering, washing, drying, and calcining after the reaction is completed to obtain a carbon-coated silicon-based core;
[0016] S3. Add the carbon-coated silicon-based core in step S2 to an ethanol aqueous solution, then add vinyltrimethoxysilane, and react at 60-70°C for 2-3h. After the reaction is completed, add 2-mercaptobenzothiazole and azobisisobutyronitrile, and heat to react. After the reaction is completed, add allylthiourea, and continue to react at 65-75°C for 1-2h. After the reaction is completed, filter, wash, and dry to obtain a silicon-based material.
[0017] Preferably, the fluoride in step S1 is at least one of magnesium fluoride, lithium fluoride, polyvinylidene fluoride and polytetrafluoroethylene.
[0018] Preferably, in step S1, the mass ratio of silicon oxide to fluoride is 100:6-12, the calcination temperature is 400-500° C., and the calcination time is 5-8 hours.
[0019] In the present invention, a silicon-based core fluorinated interface is formed on the silicon-based surface by calcination to form a strong covalent Si-F bond. On the one hand, a chemically stable protective layer can be provided to inhibit direct contact and side reactions between silicon and the electrolyte. On the other hand, the fluorinated interface can promote the formation of a stable and conductive SEI film. At the same time, the strong electronegativity of fluorine atoms is conducive to the rapid transmission of lithium ions at the interface, thereby improving the electrochemical properties of silicon-based materials.
[0020] Preferably, the volume fraction of ethanol in the ethanol aqueous solution in step S2 is 70-80%, the mass ratio of the silicon-based core and γ-aminopropyltriethoxysilane in the coating intermediate layer is 100:5-8, the temperature of the stirring reaction is 55-65°C, and the time is 2-3h.
[0021] Preferably, in step S2, the mass ratio of the solid product, deionized water, carboxymethyl cellulose, EDC and NHS is 100:900-1200:6-8.5:30-40:50-60, the temperature of the isothermal reaction is 80-90°C, the time is 3-4h, and the temperature of the calcination is 700-800°C, and the time is 2-3h.
[0022] In the present invention, carboxymethyl cellulose is connected to the middle layer through the action of chemical bonds and then carbonized to obtain a carbon coating layer, so that the carbon coating layer can be more tightly connected to the silicon-based material and is not easy to fall off, thereby improving the stability of the silicon-based material.
[0023] Specifically, the present invention adds a specific amount of carboxymethyl cellulose as a carbon source so that the thickness of the prepared carbon coating layer is moderate. If the amount added is too little, the thickness of the obtained carbon layer is too thin, which may lead to insufficient buffering effect on the volume expansion of the silicon-based material, so that the carbon layer is prone to cracking and damage, and the stability of the silicon-based material is deteriorated. If the amount added is too much, the thickness of the obtained carbon layer is too thick, which will lead to the formation of a relatively dense carbon layer, which is easy to break. At the same time, the transmission capacity with the electrolyte will also be reduced, the distance between the silicon-based cores will become larger, and the conduction of ions and electrons will become weaker.
[0024] Preferably, the volume fraction of ethanol in the ethanol aqueous solution in step S3 is 70-80%, and the mass ratio of the carbon-coated silicon-based core, vinyltrimethoxysilane, 2-mercaptobenzothiazole, allylthiourea, and azobisisobutyronitrile is 60-80:6-9:3.3-5:2.3-3.5:0.5-1.
[0025] Preferably, the heating reaction in step S3 is carried out at a temperature of 65-75° C. and for a time of 1-2 h.
[0026] In the present invention, 2-mercaptobenzothiazole and allylthiourea are introduced into the silicon-based material by chemical grafting, and a protective layer with special functional groups is formed on the surface of the silicon-based material. The introduced benzothiazole can improve the hydrophobicity of the carbon layer surface and the wettability of the interface between the electrode and the electrolyte, thereby improving the transmission efficiency of lithium ions at the interface; the thiourea group forms a strong coordination effect with the lithium ions, accelerating the transmission of lithium ions at the interface, and the thiourea group can also participate in the formation of a stable SEI film and inhibit excessive decomposition of the electrolyte, so that the silicon-based negative electrode material exhibits higher coulombic efficiency, better rate performance and cycle stability.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The silicon-based material for the battery negative electrode provided by the present invention is prepared by fluorinating the silicon-based core to form a silicon-based core fluorination interface, and then using a chemical reaction to introduce a carbon source into the silicon-based material in the form of a chemical bond to improve the stability of the carbon coating layer. Finally, specific functional groups are introduced into the carbon coating layer to significantly reduce the volume expansion of the silicon-based material through the synergistic effect between the groups. At the same time, it helps to form a stable and uniform SEI film during the battery cycle, and has good ionic conductivity, specific capacity and cycle stability.
[0029] (2) The silicon-based material for the negative electrode of the battery provided by the present invention is calcined to form a silicon-based core fluorinated interface on the silicon-based surface to form a strong covalent Si-F bond. On the one hand, it can provide a chemically stable protective layer to inhibit direct contact and side reactions between silicon and the electrolyte. On the other hand, the fluorinated interface can promote the formation of a stable and conductive SEI film. At the same time, the strong electronegativity of fluorine atoms is conducive to the rapid transmission of lithium ions at the interface. The fluorinated interface can also provide a certain mechanical buffering effect to adapt to the volume change of the silicon material during the charge and discharge process. These synergistic effects enable the silicon-based material to have higher rate performance, better cycle stability and lower interface impedance; then, the carboxymethyl cellulose is connected to the intermediate layer through the action of chemical bonds, and then carbonized to obtain a carbon coating layer, so that the carbon coating layer can be more tightly connected to the silicon-based material and is not easy to fall off, thereby improving the stability of the silicon-based material.
[0030] (3) The silicon-based material for the negative electrode of the battery provided by the present invention is characterized in that 2-mercaptobenzothiazole and allylthiourea are introduced into the silicon-based material by chemical grafting, and a protective layer with special functional groups is formed on the surface of the silicon-based material. The introduced benzothiazole can improve the hydrophobicity of the carbon layer surface and improve the wettability of the interface between the electrode and the electrolyte, thereby improving the transmission efficiency of lithium ions at the interface; the C=S and NH groups in the introduced thiourea groups form a strong coordination effect with lithium ions, which can not only provide abundant lithium ion adsorption sites to accelerate the transmission of lithium ions at the interface, but also the polar groups of thiourea can improve the lithium affinity and wettability of the carbon layer surface, which is beneficial to the uniform penetration of the electrolyte, and the thiourea groups can also participate in the formation of a stable SEI film and inhibit excessive decomposition of the electrolyte; the 2-mercaptobenzothiazole and allylthiourea on the carbon coating layer work synergistically, so that the silicon-based negative electrode material exhibits higher coulombic efficiency, better rate performance and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a SEM image of the silicon-based material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] In the present invention, the particle size of silicon monoxide is 2-5 μm.
[0034] Example 1
[0035] A method for preparing a silicon-based material for a battery negative electrode sheet comprises the following steps:
[0036] S1, 100g of silicon dioxide and 10g of lithium fluoride were mixed, and calcined at 450°C in a nitrogen atmosphere for 7h to obtain a silicon-based core coated with an intermediate layer;
[0037] S2, adding 100g of the silicon-based core of the coated intermediate layer obtained in step S1 to 900g of ethanol aqueous solution (the volume fraction of ethanol is 75%), then adding 7g of γ-aminopropyltriethoxysilane, stirring and reacting at 60°C for 2.5h, filtering, washing and drying after the reaction is completed to obtain a solid product; then adding 100g of the solid product to 1100g of deionized water, then adding 8g of carboxymethyl cellulose, 35g of EDC and 55g of NHS, reacting at a constant temperature of 85°C for 3.5h, filtering, washing and drying after the reaction is completed, and calcining at 750°C for 2.5h to obtain a carbon-coated silicon-based core;
[0038] S3. Add 70g of the carbon-coated silicon-based core in step S2 to 900g of ethanol aqueous solution (the volume fraction of ethanol is 75%), then add 8g of vinyltrimethoxysilane, and react at 65°C for 2.5h. After the reaction is completed, add 4.5g of 2-mercaptobenzothiazole and 0.8g of azobisisobutyronitrile, and react at 70°C for 1.5h. Then add 3g of allylthiourea, and continue to react at 70°C for 1.5h. After the reaction is completed, filter, wash, and dry to obtain a silicon-based material.
[0039] Example 2
[0040] A method for preparing a silicon-based material for a battery negative electrode sheet comprises the following steps:
[0041] S1, 100g of silicon dioxide and 8g of polyvinylidene fluoride were mixed, and calcined at 450°C in a nitrogen atmosphere for 6h to obtain a silicon-based core coated with an intermediate layer;
[0042] S2, adding 100g of the silicon-based core of the coated intermediate layer obtained in step S1 to 900g of ethanol aqueous solution (the volume fraction of ethanol is 75%), then adding 6g of γ-aminopropyltriethoxysilane, stirring and reacting at 60°C for 2.5h, filtering, washing and drying after the reaction is completed to obtain a solid product; then adding 100g of the solid product to 1000g of deionized water, then adding 7g of carboxymethyl cellulose, 35g of EDC and 55g of NHS, reacting at a constant temperature of 85°C for 3.5h, filtering, washing and drying after the reaction is completed, and calcining at 750°C for 2.5h to obtain a carbon-coated silicon-based core;
[0043] S3. Add 70g of the carbon-coated silicon-based core in step S2 to 900g of ethanol aqueous solution (the volume fraction of ethanol is 75%), then add 7g of vinyltrimethoxysilane, and react at 65°C for 2.5h. After the reaction is completed, add 3.5g of 2-mercaptobenzothiazole and 0.7g of azobisisobutyronitrile, and react at 70°C for 1.5h. Then add 2.7g of allylthiourea, and continue to react at 70°C for 1.5h. After the reaction is completed, filter, wash, and dry to obtain a silicon-based material.
[0044] Example 3
[0045] A method for preparing a silicon-based material for a battery negative electrode sheet comprises the following steps:
[0046] S1, 100g of silicon dioxide and 6g of magnesium fluoride were mixed, and calcined at 400°C in a nitrogen atmosphere for 8h to obtain a silicon-based core coated with an intermediate layer;
[0047] S2, adding 100g of the silicon-based core of the coated intermediate layer obtained in step S1 to 900g of ethanol aqueous solution (the volume fraction of ethanol is 70%), then adding 5g of γ-aminopropyltriethoxysilane, stirring and reacting at 55°C for 3h, filtering, washing and drying after the reaction is completed to obtain a solid product; then adding 100g of the solid product to 900g of deionized water, then adding 6g of carboxymethyl cellulose, 30g of EDC, and 50g of NHS, reacting at a constant temperature of 80°C for 4h, filtering, washing, drying after the reaction is completed, and calcining at 700°C for 3h to obtain a carbon-coated silicon-based core;
[0048] S3. Add 60g of the carbon-coated silicon-based core in step S2 to 900g of ethanol aqueous solution (the volume fraction of ethanol is 70%), then add 6g of vinyltrimethoxysilane, and react at 60°C for 3h. After the reaction is completed, add 3.3g of 2-mercaptobenzothiazole and 0.5g of azobisisobutyronitrile, and react at 65°C for 2h. Then add 2.3g of allylthiourea and continue to react at 65°C for 2h. After the reaction is completed, filter, wash and dry to obtain a silicon-based material.
[0049] Example 4
[0050] A method for preparing a silicon-based material for a battery negative electrode sheet comprises the following steps:
[0051] S1, 100g of silicon dioxide and 12g of polytetrafluoroethylene were mixed, and calcined at 500°C for 5h in a nitrogen atmosphere to obtain a silicon-based core coated with an intermediate layer;
[0052] S2, adding 100g of the silicon-based core of the coated intermediate layer obtained in step S1 to 900g of ethanol aqueous solution (the volume fraction of ethanol is 80%), then adding 8g of γ-aminopropyltriethoxysilane, stirring and reacting at 65°C for 2h, filtering, washing and drying after the reaction is completed to obtain a solid product; then adding 100g of the solid product to 1200g of deionized water, then adding 8.5g of carboxymethyl cellulose, 40g of EDC and 60g of NHS, reacting at a constant temperature of 90°C for 3h, filtering, washing and drying after the reaction is completed, and calcining at 800°C for 2h to obtain a carbon-coated silicon-based core;
[0053] S3. Add 80g of the carbon-coated silicon-based core in step S2 to 900g of ethanol aqueous solution (the volume fraction of ethanol is 80%), then add 9g of vinyltrimethoxysilane, and react at 70°C for 2h. After the reaction is completed, add 5g of 2-mercaptobenzothiazole and 1g of azobisisobutyronitrile, and react at 75°C for 1h. Then add 3.5g of allylthiourea and continue to react at 75°C for 1h. After the reaction is completed, filter, wash and dry to obtain a silicon-based material.
[0054] Comparative Example 1
[0055] A method for preparing a silicon-based material for a battery negative electrode sheet comprises the following steps:
[0056] S1, 100g of silicon dioxide and 10g of lithium fluoride were mixed, and calcined at 450°C in a nitrogen atmosphere for 7h to obtain a silicon-based core coated with an intermediate layer;
[0057] S2, adding 100g of the silicon-based core of the coated intermediate layer obtained in step S1 to 1100g of deionized water, followed by adding 8g of carboxymethyl cellulose, stirring at 85°C for 3.5h, filtering, washing, and drying after the reaction is completed, and calcining at 750°C for 2.5h to obtain a carbon-coated silicon-based core;
[0058] S3. Add 70g of the carbon-coated silicon-based core in step S2 to 900g of ethanol aqueous solution (the volume fraction of ethanol is 75%), then add 8g of vinyltrimethoxysilane, and react at 65°C for 2.5h. After the reaction is completed, add 4.5g of 2-mercaptobenzothiazole and 0.8g of azobisisobutyronitrile, and react at 70°C for 1.5h. Then add 3g of allylthiourea, and continue to react at 70°C for 1.5h. After the reaction is completed, filter, wash, and dry to obtain a silicon-based material.
[0059] Compared with Example 1, the carbon coating layer and the intermediate layer in this comparative example are prepared by physical coating.
[0060] Comparative Example 2
[0061] A method for preparing a silicon-based material for a battery negative electrode sheet comprises the following steps:
[0062] S1, 100g of silicon dioxide and 10g of lithium fluoride were mixed, and calcined at 450°C in a nitrogen atmosphere for 7h to obtain a silicon-based core coated with an intermediate layer;
[0063] S2, adding 100g of the silicon-based core of the coated intermediate layer obtained in step S1 to 900g of ethanol aqueous solution (the volume fraction of ethanol is 75%), then adding 7g of γ-aminopropyltriethoxysilane, stirring and reacting at 60°C for 2.5h, filtering, washing and drying after the reaction is completed to obtain a solid product; then adding 100g of the solid product to 1100g of deionized water, then adding 8g of carboxymethyl cellulose, 35g of EDC and 55g of NHS, reacting at a constant temperature of 85°C for 3.5h, filtering, washing and drying after the reaction is completed, and calcining at 750°C for 2.5h to obtain a carbon-coated silicon-based core;
[0064] S3. Add 70g of the carbon-coated silicon-based core in step S2 into 900g of ethanol aqueous solution (the volume fraction of ethanol is 75%), then add 8g of vinyltrimethoxysilane, and react at 65°C for 2.5h. After the reaction is completed, add 4.5g of 2-mercaptobenzothiazole and 0.8g of azobisisobutyronitrile, and react at 70°C for 1.5h. After the reaction is completed, filter, wash, and dry to obtain a silicon-based material.
[0065] Compared with Example 1, allylthiourea is not grafted onto the carbon coating layer in this comparative example.
[0066] Comparative Example 3
[0067] A method for preparing a silicon-based material for a battery negative electrode sheet comprises the following steps:
[0068] S1, 100g of silicon dioxide and 10g of lithium fluoride were mixed, and calcined at 450°C in a nitrogen atmosphere for 7h to obtain a silicon-based core coated with an intermediate layer;
[0069] S2, adding 100g of the silicon-based core of the coated intermediate layer obtained in step S1 to 900g of ethanol aqueous solution (the volume fraction of ethanol is 75%), then adding 7g of γ-aminopropyltriethoxysilane, stirring and reacting at 60°C for 2.5h, filtering, washing and drying after the reaction is completed to obtain a solid product; then adding 100g of the solid product to 1100g of deionized water, then adding 8g of carboxymethyl cellulose, 35g of EDC and 55g of NHS, reacting at a constant temperature of 85°C for 3.5h, filtering, washing and drying after the reaction is completed, and calcining at 750°C for 2.5h to obtain a carbon-coated silicon-based core;
[0070] S3. Add 70g of carbon-coated silicon-based core in step S2 into 900g of ethanol aqueous solution (the volume fraction of ethanol is 75%), then add 8g of vinyltrimethoxysilane, and react at 65°C for 2.5h. After the reaction is completed, add 3g of allylthiourea and continue to react at 70°C for 1.5h. After the reaction is completed, filter, wash and dry to obtain a silicon-based material.
[0071] Compared with Example 1, in this comparative example, 2-mercaptobenzothiazole is not grafted onto the carbon coating layer.
[0072] Comparative Example 4
[0073] A method for preparing a silicon-based material for a battery negative electrode sheet comprises the following steps:
[0074] S1, 100g of silicon dioxide and 10g of lithium fluoride were mixed, and calcined at 450°C in a nitrogen atmosphere for 7h to obtain a silicon-based core coated with an intermediate layer;
[0075] S2, adding 100g of the silicon-based core of the coated intermediate layer obtained in step S1 to 900g of ethanol aqueous solution (the volume fraction of ethanol is 75%), then adding 7g of γ-aminopropyltriethoxysilane, stirring and reacting at 60°C for 2.5h, filtering, washing and drying after the reaction is completed to obtain a solid product; then adding 100g of the solid product to 1100g of deionized water, then adding 8g of carboxymethyl cellulose, 35g of EDC and 55g of NHS, reacting at a constant temperature of 85°C for 3.5h, filtering, washing and drying after the reaction is completed, and calcining at 750°C for 2.5h to obtain a carbon-coated silicon-based core;
[0076] S3. Add 70g of the carbon-coated silicon-based core in step S2 into 900g of ethanol aqueous solution (the volume fraction of ethanol is 75%), then add 8g of vinyltrimethoxysilane, and react at 65°C for 2.5h. After the reaction is completed, filter, wash and dry to obtain a silicon-based material.
[0077] Compared with Example 1, in this comparative example, 2-mercaptobenzothiazole and allylthiourea are not grafted onto the carbon coating layer.
[0078] The silicon-based materials prepared in Examples 1-4 and Comparative Examples 1-4 were subjected to performance tests, as follows:
[0079] Weigh 0.4 g of the silicon-based material prepared in Examples 1-4 and Comparative Examples 1-4, 50 mg of carboxymethyl cellulose and 50 mg of conductive agent Super P respectively, add appropriate amount of deionized water and use a planetary ball mill to ball mill for 2 h, apply the milled slurry on the current collector, vacuum dry it at 80 ° C for 12 h, and cut it into negative electrode sheets with a diameter of 12 mm. Metal lithium is used as the counter electrode and reference electrode, a glass fiber diaphragm is used as the diaphragm, and a LiPF6 electrolyte with a concentration of 1 mol / L is used. The solvent is a mixed solution of diethyl carbonate and ethylene carbonate (volume ratio of 1:1), and the button batteries are assembled in a glove box with an argon atmosphere.
[0080] Resistivity test method: Use a two-probe resistance meter to test; Charge and discharge efficiency (Coulomb efficiency) test: Cycle the assembled lithium-ion button cell at a current density of 0.2A / g in the voltage range of 0.005V-2V to obtain the charge and discharge capacity. Charge and discharge efficiency = charge capacity / discharge capacity × 100%; Cycle stability: Under normal temperature conditions, use 0.5C / 0.5C charge and discharge cycles. Capacity retention rate after 500 cycles = 500th charge capacity / first charge capacity × 100%. The test results are shown in Table 1 below:
[0081] Table 1 Battery electrochemical performance data of Examples 1-4 and Comparative Examples 1-4
[0082]
[0083]
[0084] As can be seen from Table 1 above, the battery prepared using the silicon-based material prepared by the present invention has a smaller resistivity and internal resistance. Compared with Comparative Examples 1-4, the first discharge specific capacity, the first coulombic efficiency and the cycle performance are significantly improved, indicating that the silicon-based material prepared by the present invention has good ionic conductivity and stability, and helps to form a stable and uniform SEI film during the battery cycle, thereby improving the cycle stability of the battery.
[0085] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A silicon-based material for a battery negative electrode, characterized in that: The silicon-based material includes a silicon-based core, an intermediate layer and a carbon coating layer from the inside to the outside; The carbon coating layer is connected to the middle layer through a chemical bond, and a functional compound is grafted onto the surface of the carbon coating layer.
2. The silicon-based material for battery negative electrode according to claim 1, characterized in that: The silicon-based core is silicon monoxide, and the intermediate layer is fluoride.
3. The silicon-based material for battery negative electrode according to claim 1, characterized in that: The carbon source in the carbon coating layer is carboxymethyl cellulose, and the functional compounds are 2-mercaptobenzothiazole and allylthiourea.
4. A method for preparing a silicon-based material for a negative electrode sheet of a battery as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: S1, mixing silicon oxide and fluoride, and then calcining to obtain a silicon-based core coated with an intermediate layer; S2, adding the silicon-based core of the coated intermediate layer obtained in step S1 to an ethanol aqueous solution, then adding γ-aminopropyltriethoxysilane, stirring to react, filtering, washing, and drying after the reaction is completed to obtain a solid product; then adding the solid product to deionized water, then adding carboxymethyl cellulose, EDC, and NHS to react at a constant temperature, filtering, washing, drying, and calcining after the reaction is completed to obtain a carbon-coated silicon-based core; S3. Add the carbon-coated silicon-based core in step S2 to an ethanol aqueous solution, then add vinyltrimethoxysilane, and react at 60-70°C for 2-3h. After the reaction is completed, add 2-mercaptobenzothiazole and azobisisobutyronitrile, and heat to react. After the reaction is completed, add allylthiourea, and continue to react at 65-75°C for 1-2h. After the reaction is completed, filter, wash, and dry to obtain a silicon-based material.
5. The preparation method according to claim 4, characterized in that: The fluoride in step S1 is at least one of magnesium fluoride, lithium fluoride, polyvinylidene fluoride and polytetrafluoroethylene.
6. The preparation method according to claim 4, characterized in that: In step S1, the mass ratio of silicon oxide to fluoride is 100:6-12, the calcination temperature is 400-500° C., and the calcination time is 5-8 hours.
7. The preparation method according to claim 4, characterized in that: The volume fraction of ethanol in the ethanol aqueous solution in step S2 is 70-80%, the mass ratio of the silicon-based core and γ-aminopropyltriethoxysilane in the coating intermediate layer is 100:5-8, the temperature of the stirring reaction is 55-65°C, and the time is 2-3h.
8. The preparation method according to claim 4, characterized in that: The mass ratio of the solid product, deionized water, carboxymethyl cellulose, EDC and NHS in step S2 is 100:900-1200:6-8.5:30-40:50-60, the temperature of the isothermal reaction is 80-90°C, the time is 3-4h, and the temperature of the calcination is 700-800°C, and the time is 2-3h.
9. The preparation method according to claim 4, characterized in that: The volume fraction of ethanol in the ethanol aqueous solution in step S3 is 70-80%, and the mass ratio of the carbon-coated silicon-based core, vinyltrimethoxysilane, 2-mercaptobenzothiazole, allylthiourea, and azobisisobutyronitrile is 60-80:6-9:3.3-5:2.3-3.5:0.5-1.
10. The preparation method according to claim 4, characterized in that: The heating reaction temperature in step S3 is 65-75° C. and the time is 1-2 h.
Citation Information
Patent Citations
Silicon-based negative electrode material and preparation method thereof
CN105118974A
Silicon-based material and preparation method thereof, negative pole piece and battery
CN117438562A